An index of inguinal and inguinofemoral masses in women: Critical considerations for diagnosis - Jason Gandhi; Saher Zaidi; Yiji Suh; Gunjan Joshi; Noel L. Smith; Sardar Ali Khan (Translational Research in Anatomy, 2018)
A range of masses can manifest in the region encompassing the femoral triangle and the inguinal canal in women. These groin masses can be classified as being neoplasms, infectious or inflammatory processes, vascular conditions, as well as congenital abnormalities. Such inguinal masses can cause aching and pain sensations in the groin region, which can worsen after prolonged activity. A comprehensive history and physical examination are sufficient in making a diagnosis of the type of inguinal mass. Imaging modalities such as computed tomography, ultrasonography, or magnetic resonance imaging demonstrate a better understanding of local anatomical characteristics of the inguinal area, allowing for a diagnosis and the characterization of the groin pathologic conditions. Most inguinal masses are often repaired or need surgical intervention through open or laparoscopic technique. A combination of the clinical history, anatomical classification, and unique imaging features can aid clinicians in an accurate diagnosis of the inguinal or inguinofemoral mass in the female groin region. Keywords: Groin, Inguinal mass, Inguinofemoral mass, Inguinal canal, Round ligament varicosities, Inguinal hernia, Femoral hernia, Femoral triangle, Laparoscopic surgery